Enrichment of Whole Wheat Cocoa Biscuits with Encapsulated Grape Skin Extract - Roberta Dordoni; Guillermo Duserm Garrido; Laura Marinoni; Luisa Torri; Maria Piochi; Giorgia Spigno (International Journal of Food Science)
Grape pomace is one of the major waste products generated by the wine-making process and it contains seeds and skins still rich in bioactive compounds. Skins can be separated from the seeds and valorised for the recovery of antioxidant extracts with different potential applications. The aim of this study was to evaluate the influence of the addition of an extract obtained from waste grape skins and encapsulated in maltodextrins on the antioxidant properties and sensory acceptability of whole wheat cocoa biscuits. Different levels of enrichment (1.2, 2.3, and 3.5% on dough weight) were tested, and the obtained doughs and biscuits were analysed for total phenols content and antioxidant capacity (based on different radical assays). Extract addition increased the phenolic content (up to 134% increase) and antioxidant capacity (up to 244%) of both doughs and biscuits. Extract containing biscuits were also characterised by a different colour. However, oxidation stability, evaluated at accelerated temperature and oxygen conditions, was not improved by the extract incorporation. Cooking led to an average (not always significant) 16% decrease in phenolic content for both enriched and reference recipes. The enrichment level significantly influenced the sensory acceptability, with identification of two clusters of consumers, with one cluster preferring the biscuits with the highest enrichment level and one cluster preferring the biscuits with the lowest level. The results showed that whole wheat cacao biscuits represent an appropriate food matrix to develop pleasant novel products enriched in phenolic compounds from waste grape skins and likeable for regular biscuits consumers.